--- /dev/null
+(**************************************************************************)
+(* ___ *)
+(* ||M|| *)
+(* ||A|| A project by Andrea Asperti *)
+(* ||T|| *)
+(* ||I|| Developers: *)
+(* ||T|| The HELM team. *)
+(* ||A|| http://helm.cs.unibo.it *)
+(* \ / *)
+(* \ / This file is distributed under the terms of the *)
+(* v GNU General Public License Version 2 *)
+(* *)
+(**************************************************************************)
+
+set "baseuri" "cic:/matita/demo/power_derivative".
+
+include "nat/plus.ma".
+include "nat/orders.ma".
+include "nat/compare.ma".
+
+axiom R: Type.
+axiom R0: R.
+axiom R1: R.
+axiom Rplus: R→R→R.
+axiom Rmult: R→R→R.
+
+notation "0" with precedence 89
+for @{ 'zero }.
+interpretation "Rzero" 'zero =
+ (cic:/matita/demo/power_derivative/R0.con).
+interpretation "Nzero" 'zero =
+ (cic:/matita/nat/nat/nat.ind#xpointer(1/1/1)).
+
+notation "1" with precedence 89
+for @{ 'one }.
+interpretation "Rone" 'one =
+ (cic:/matita/demo/power_derivative/R1.con).
+interpretation "None" 'one =
+ (cic:/matita/nat/nat/nat.ind#xpointer(1/1/2)
+ cic:/matita/nat/nat/nat.ind#xpointer(1/1/1)).
+
+interpretation "Rplus" 'plus x y =
+ (cic:/matita/demo/power_derivative/Rplus.con x y).
+interpretation "Rmult" 'times x y =
+ (cic:/matita/demo/power_derivative/Rmult.con x y).
+
+definition Fplus ≝
+ λf,g:R→R.λx:R.f x + g x.
+
+definition Fmult ≝
+ λf,g:R→R.λx:R.f x * g x.
+
+interpretation "Fplus" 'plus x y =
+ (cic:/matita/demo/power_derivative/Fplus.con x y).
+interpretation "Fmult" 'times x y =
+ (cic:/matita/demo/power_derivative/Fmult.con x y).
+
+notation "2" with precedence 89
+for @{ 'two }.
+interpretation "Rtwo" 'two =
+ (cic:/matita/demo/power_derivative/Rplus.con
+ cic:/matita/demo/power_derivative/R1.con
+ cic:/matita/demo/power_derivative/R1.con).
+interpretation "Ntwo" 'two =
+ (cic:/matita/nat/nat/nat.ind#xpointer(1/1/2)
+ (cic:/matita/nat/nat/nat.ind#xpointer(1/1/2)
+ (cic:/matita/nat/nat/nat.ind#xpointer(1/1/1)))).
+
+let rec Rpower (x:R) (n:nat) on n ≝
+ match n with
+ [ O ⇒ 1
+ | S n ⇒ x * (Rpower x n)
+ ].
+
+interpretation "Rpower" 'exp x n =
+ (cic:/matita/demo/power_derivative/Rpower.con x n).
+
+let rec inj (n:nat) on n : R ≝
+ match n with
+ [ O ⇒ 0
+ | S n ⇒
+ match n with
+ [ O ⇒ 1
+ | S m ⇒ 1 + inj n
+ ]
+ ].
+
+coercion cic:/matita/demo/power_derivative/inj.con.
+
+axiom Rplus_Rzero_x: ∀x:R.0+x=x.
+axiom Rplus_comm: symmetric ? Rplus.
+axiom Rplus_assoc: associative ? Rplus.
+axiom Rmult_Rone_x: ∀x:R.1*x=x.
+axiom Rmult_Rzero_x: ∀x:R.0*x=0.
+axiom Rmult_assoc: associative ? Rmult.
+axiom Rmult_comm: symmetric ? Rmult.
+axiom Rmult_Rplus_distr: distributive ? Rmult Rplus.
+
+alias symbol "times" = "Rmult".
+alias symbol "plus" = "natural plus".
+
+definition monomio ≝
+ λn.λx:R.x\sup n.
+
+definition costante : nat → R → R ≝
+ λa:nat.λx:R.inj a.
+
+coercion cic:/matita/demo/power_derivative/costante.con 1.
+
+axiom f_eq_extensional:
+ ∀f,g:R→R.(∀x:R.f x = g x) → f=g.
+
+lemma Fmult_one_f: ∀f:R→R.1*f=f.
+ intro;
+ unfold Fmult;
+ simplify;
+ apply f_eq_extensional;
+ intro;
+ auto.
+qed.
+
+lemma Fmult_zero_f: ∀f:R→R.0*f=0.
+ intro;
+ unfold Fmult;
+ simplify;
+ apply f_eq_extensional;
+ intro;
+ auto.
+qed.
+
+lemma Fmult_commutative: symmetric ? Fmult.
+ unfold;
+ intros;
+ unfold Fmult;
+ apply f_eq_extensional;
+ intros;
+ auto.
+qed.
+
+lemma Fmult_associative: associative ? Fmult.
+ unfold;
+ intros;
+ unfold Fmult;
+ unfold Fmult;
+ apply f_eq_extensional;
+ intros;
+ auto.
+qed.
+
+lemma Fmult_Fplus_distr: distributive ? Fmult Fplus.
+ unfold;
+ intros;
+ unfold Fmult;
+ unfold Fplus;
+ apply f_eq_extensional;
+ intros;
+ simplify;
+ auto.
+qed.
+
+lemma monomio_product:
+ ∀n,m.monomio (n+m) = monomio n * monomio m.
+ intros;
+ unfold monomio;
+ unfold Fmult;
+ simplify;
+ elim n;
+ [ simplify;
+ apply f_eq_extensional;
+ intro;
+ auto
+ | simplify;
+ apply f_eq_extensional;
+ intro;
+ cut (x\sup (n1+m) = x \sup n1 * x \sup m);
+ [ rewrite > Hcut;
+ auto
+ | change in ⊢ (? ? % ?) with ((λx:R.(x)\sup(n1+m)) x);
+ rewrite > H;
+ reflexivity
+ ]
+ ].
+qed.
+
+lemma costante_sum:
+ ∀n,m.costante n + costante m = costante (n+m).
+ intros;
+ unfold Fplus;
+ unfold costante;
+ apply f_eq_extensional;
+ intros;
+ elim n;
+ [ simplify;
+ auto
+ | simplify;
+ clear x;
+ clear H;
+ clear n;
+ elim n1;
+ [ simplify;
+ elim m;
+ [ simplify;
+ auto
+ | simplify;
+ rewrite < H;
+ auto
+ ]
+ | simplify;
+ rewrite < H;
+ clear H;
+ elim n;
+ [ simplify;
+ auto
+ | simplify;
+ auto
+ ]
+ ]
+ ].
+qed.
+
+axiom derivative: (R→R) → R → R.
+
+notation "hvbox('D'[f])"
+ non associative with precedence 90
+for @{ 'derivative $f }.
+
+interpretation "Rderivative" 'derivative f =
+ (cic:/matita/demo/power_derivative/derivative.con f).
+
+notation "hvbox('x' \sup n)"
+ non associative with precedence 60
+for @{ 'monomio $n }.
+
+notation "hvbox('x')"
+ non associative with precedence 60
+for @{ 'monomio 1 }.
+
+interpretation "Rmonomio" 'monomio n =
+ (cic:/matita/demo/power_derivative/monomio.con n).
+
+axiom derivative_x0: D[x \sup 0] = 0.
+axiom derivative_x1: D[x] = 1.
+axiom derivative_mult: ∀f,g:R→R. D[f*g] = D[f]*g + f*D[g].
+
+alias symbol "times" = "Fmult".
+
+theorem derivative_power: ∀n:nat. D[x \sup n] = n*x \sup (pred n).
+ assume n:nat.
+ we proceed by induction on n to prove
+ (D[x \sup n] = n*x \sup (pred n)).
+ case O.
+ the thesis becomes (D[x \sup 0] = 0*x \sup (pred 0)).
+ by _
+ done.
+ case S (m:nat).
+ by induction hypothesis we know
+ (D[x \sup m] = m*x \sup (pred m)) (H).
+ the thesis becomes
+ (D[x \sup (1+m)] = (1+m)*x \sup m).
+ we need to prove
+ (m * (x \sup (1+ pred m)) = m * x \sup m) (Ppred).
+ by _ we proved (0 < m ∨ 0=m) (cases).
+ we proceed by induction on cases
+ to prove (m * (x \sup (1+ pred m)) = m * x \sup m).
+ case left.
+ suppose (0 < m) (m_pos).
+ by (S_pred m m_pos) we proved (m = 1 + pred m) (H1).
+ by _
+ done.
+ case right.
+ suppose (0=m) (m_zero). by _ done.
+ conclude
+ (D[x \sup (1+m)])
+ = (D[x * x \sup m]) by _.
+ = (D[x] * x \sup m + x * D[x \sup m]) by _.
+ = (x \sup m + x * (m * x \sup (pred m))) by _.
+clear H.
+ = (x \sup m + m * (x \sup (1 + pred m))) by _.
+ = (x \sup m + m * x \sup m) by _.
+ = ((1+m)*x \sup m) by _ (timeout=30)
+ done.
+qed.
+
+notation "hvbox(\frac 'd' ('d' ident i) break p)"
+ right associative with precedence 90
+for @{ 'derivative ${default
+ @{\lambda ${ident i} : $ty. $p)}
+ @{\lambda ${ident i} . $p}}}.
+
+interpretation "Rderivative" 'derivative \eta.f =
+ (cic:/matita/demo/power_derivative/derivative.con f).
+
+theorem derivative_power': ∀n:nat. D[x \sup (1+n)] = (1+n)*x \sup n.
+ assume n:nat.
+ we proceed by induction on n to prove
+ (D[x \sup (1+n)] = (1+n)*x \sup n).
+ case O.
+ the thesis becomes (D[x \sup 1] = 1*x \sup 0).
+ by _
+ done.
+ case S (m:nat).
+ by induction hypothesis we know
+ (D[x \sup (1+m)] = (1+m)*x \sup m) (H).
+ the thesis becomes
+ (D[x \sup (2+m)] = (2+m)*x \sup (1+m)).
+ conclude
+ (D[x \sup (2+m)])
+ = (D[x \sup 1 * x \sup (1+m)]) by _.
+ = (D[x \sup 1] * x \sup (1+m) + x * D[x \sup (1+m)]) by _.
+ = (x \sup (1+m) + x * (costante (1+m) * x \sup m)) by _.
+clear H.
+ = (x \sup (1+m) + costante (1+m) * x \sup (1+m)) by _.
+ = (x \sup (1+m) * (costante (2 + m))) by _
+ done.
+qed.